2022
DOI: 10.2166/nh.2022.127
|View full text |Cite
|
Sign up to set email alerts
|

Neural network model predictions for phosphorus management strategies on tile-drained organic soils

Abstract: The organic soils of Holland Marsh, Ontario are used for intensive vegetable production, which demands high-phosphorus (P) fertilizer applications. Such high-fertilizer applications on these tile-drained lands lead to eutrophication in surrounding water bodies. This study investigated the application of neural network (NN) models for deriving P management strategies. Seven NN models were assessed using the following two approaches: a time series with 1-year training and 1-year testing of the models and a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Many have promoted the use of water table management via water control structures on tile‐drained mineral soils to reduce N and P pollution (Cooke & Verma, 2012; King et al, 2022; Skaggs et al, 2012; Tan et al, 1998). Research by Grenon et al (2022) has shown that water table control on the tile‐drained organic soils of the Holland Marsh can also be effective in reducing P loads from tile drain outlets. They found that a reduction of 20% in the spring TP load can be achieved by raising the control gate level to 30 cm from the soil surface.…”
Section: Long‐term Phosphorus Reduction Through Improved Water Contro...mentioning
confidence: 99%
“…Many have promoted the use of water table management via water control structures on tile‐drained mineral soils to reduce N and P pollution (Cooke & Verma, 2012; King et al, 2022; Skaggs et al, 2012; Tan et al, 1998). Research by Grenon et al (2022) has shown that water table control on the tile‐drained organic soils of the Holland Marsh can also be effective in reducing P loads from tile drain outlets. They found that a reduction of 20% in the spring TP load can be achieved by raising the control gate level to 30 cm from the soil surface.…”
Section: Long‐term Phosphorus Reduction Through Improved Water Contro...mentioning
confidence: 99%
“…Forecasting results using the LSTM model have shown darker results than other methods (Hayder et al 2022). In addition to hydrological forecasting, LSTM models are also applied to predict substance concentrations (Grenon et al 2022), wastewater flow control (Seshan et al 2024), and precipitation (Alqahtani 2024).…”
Section: Introductionmentioning
confidence: 99%